2006
DOI: 10.1080/02699200400027015
|View full text |Cite
|
Sign up to set email alerts
|

Voice and pronunciation of cochlear implant speakers

Abstract: Patients with cochlear implants have the ability to exercise auditory control over their own speech production and over the speech of others, which is important for the development of speech control. In the present investigation three groups of 10 subjects were compared. The groups comprised: (1) cochlear implant users, (2) profoundly deaf using traditional hearing aids, and (3) hearing controls. The subjects in three groups were matched in age. While repeating after a model the subjects were recorded and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 9 publications
5
30
1
2
Order By: Relevance
“…Croatian, like Spanish, has prevoiced VOT durations for voiced stops and short-lag durations for voiceless stops (Smiljanic & Bradlow, 2008). Horga and Liker (2006) compared samples of acoustic measures, including VOT of /t/ and /d/, of 10 monolingual Croatian children with CIs with age-matched peers with hearing aids and typically developing children with NH. The results indicated that children with CIs and those with hearing aids did not contrast the VOT values of /t/ and /d/, and although the VOT durations were not significantly different between the two groups of children with hearing loss, the authors reported that pronunciation and voice quality of the CI users were perceived as better than those of the children who used hearing aids.…”
Section: Voiced and Voiceless Stop Production By CI Usersmentioning
confidence: 99%
“…Croatian, like Spanish, has prevoiced VOT durations for voiced stops and short-lag durations for voiceless stops (Smiljanic & Bradlow, 2008). Horga and Liker (2006) compared samples of acoustic measures, including VOT of /t/ and /d/, of 10 monolingual Croatian children with CIs with age-matched peers with hearing aids and typically developing children with NH. The results indicated that children with CIs and those with hearing aids did not contrast the VOT values of /t/ and /d/, and although the VOT durations were not significantly different between the two groups of children with hearing loss, the authors reported that pronunciation and voice quality of the CI users were perceived as better than those of the children who used hearing aids.…”
Section: Voiced and Voiceless Stop Production By CI Usersmentioning
confidence: 99%
“…Levels of spoken language skill previously achieved only occasionally in children who were profoundly deaf and used hearing aids have now become the norm, with higher levels seen in the areas of speech perception (Eisenberg et al, 2006), speech production (Chin, Tsai & Gao, 2003;Flipsen & Colvard, 2006;Horga & Liker, 2006;Tobey, Geers, Brenner, Altuna, & Gabbert, 2003), language (Moog, 2002;Nicholas & Geers, 2006a;2006b), and reading (Geers, 2003;Spencer, Tomblin & Gantz, 1998). Many educators and clinicians working with children who have severe-profound hearing loss are revising educational strategies and expectations based upon the general success facilitated by cochlear implant (CI) devices.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of deafness therefore might be also of importance for speech production outcome according to the DIVA theory [18]. In the present study on adult CI users' speech outcomes, we therefore focused on the role of duration of deafness and some other factors.…”
Section: Discussionmentioning
confidence: 99%
“…This comes along with the variable results on other aspects of speech such as altered nasality, voice, formants, and prosody as described by some authors concerning speech outcomes after cochlear implantation [12,16,17]. Horga and Liker [18] compared several variables such as vowel formant space, voice versus voiceless differences, closure duration and voice onset time, word accent production, sentence stress production, voice quality, and pronunciation quality in three groups of 10 subjects each: children with a CI, children with profound deafness who used traditional hearing aids, and normal-hearing subjects. The results revealed that most CI users performed worse than people with normal hearing, but better than deaf subjects with hearing aids.…”
Section: Introductionmentioning
confidence: 99%